Pengaruh Gaya Mengajar Guru Terhadap Hasil Belajar Siswa SMK - Pakomus Hutomo Gulo; Arisman Telaumbanua (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
This study examines the impact of teachers' teaching styles on students' learning outcomes. The main issue addressed in this research is how variations in teaching styles affect students' learning outcomes, which is a crucial factor in enhancing the understanding and application of knowledge. The aim of this study is to determine the effect of teachers' teaching styles on the learning outcomes of students in the subject of Construction and Building Utilities at SMK Negeri Lotu. The research method employed is a quantitative approach with a descriptive method. The sample consists of all students in the XI DPIB class, totaling 21 students. Data were collected using a Likert scale questionnaire designed to measure teachers' teaching styles and their impact on students' learning outcomes. Data analysis was conducted with validity, reliability, normality, and linearity tests to ensure the accuracy and precision of the data. The analysis results show a significant impact of teaching styles on students' learning outcomes. The study concludes that the application of appropriate teaching styles can significantly improve students' learning outcomes. The prospects of this research highlight the importance of developing and implementing innovative teaching methods that meet students' needs to enhance the quality of education, particularly in vocational education that requires practical skills and industry relevance.